Measurement and analysis of factors that affecting the financial stability of private banks registered in the Iraq Stock Exchange for the period (2017-2013) - Yousif, Rawaa Ahmad (Journal of Economic, Administrative and Legal Sciences, 2021)
The objective of this study was to measure the banking factors (capital adequacy, credit capacity, and revenue capacity) and to show their impact on the banking stability of the private banks registered in the Iraq Stock Exchange. Where the bank credit represents the most important source of bank money in terms of achieving profits and the most exposed to risks, which is reflected in the bank’s business and its financial indicators. Also, achieving ratio (adequacy of banking capital) corresponded with the guidelines of the Basel Committee for is one of the top concerns of the banking administration. Each of the (z_score) and multiple linear regression models were used to measure the stability of banks and calculated the impact of the study variables on financial stability. The research sample consisted of (6) private banks, these banks are apart of 44 private banks of registered in Iraq Stock Exchange which are operating in Iraq. The research reached to set of conclusions, including that achieving financial stability for banks depends mainly on strengthening the adequacy of capital and then its ability to achieve profits. Also, the research recommended that banks implement the decisions of the Basel Committee (first, second and third) that contribute to enhancing the financial stability of banks.
Keywords: financial stability; z-score model; multiple linear regression model